2022
DOI: 10.34172/hpp.2022.03
|View full text |Cite
|
Sign up to set email alerts
|

The role of social media during the COVID-19 pandemic: Salvaging its ‘power’ for positive social behaviour change in Africa

Abstract: The ongoing coronavirus disease 2019 (COVID-19) pandemic remains a significant global public health crisis. The unique evolution of the COVID-19 pandemic has seen social media emerging and growing into an important vehicle for rapid information dissemination. This has in turn given rise to multiple sources of information, leading to what has come to be known as ‘infodemic’, associated with the plethora of misinformation and conspiracy theories. In this perspective, we explore the growth of the social media ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 25 publications
0
21
0
Order By: Relevance
“…Social media provides a powerful platform through which people’s attitudes and behaviours may be influenced both positively and negatively in relation to socio-political issues (Lozano-Blasco et al , 2022). Social media posts have been shown to influence off-line behaviour in terms of increasing xenophobia (Madziva et al , 2022), unhealthy restriction of eating (Rounsefell et al , 2020), gang-related violence and self-harm/suicide (House of Commons Social Media Enquiry, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Social media provides a powerful platform through which people’s attitudes and behaviours may be influenced both positively and negatively in relation to socio-political issues (Lozano-Blasco et al , 2022). Social media posts have been shown to influence off-line behaviour in terms of increasing xenophobia (Madziva et al , 2022), unhealthy restriction of eating (Rounsefell et al , 2020), gang-related violence and self-harm/suicide (House of Commons Social Media Enquiry, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…For adolescents, social media is also considered a platform to engage in social comparison (Stockdale and Coyne, 2020), self-disclosure and identity construction (Davis, 2012). Social media posts have also been shown to influence off-line behaviour in terms of increasing xenophobia (Madziva et al , 2022), unhealthy restriction of eating (Rounsefell et al , 2020), gang-related violence and self-harm/suicide (House of Commons Social Media Enquiry, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Blankenship et al (2018) examined the tweets with the "vaccine" hashtag (#vaccine) from 2010 to 2016 and concluded that anti-vaccine tweets were 4.13-fold more likely to be re-tweeted than neutral tweets. Madziva et al (2022) explored the contextual interdependence of social media platforms and behavioral changes in Africa. According to the study, behavioral change is a process where when netizens are exposed to messages on social media, they are not always influenced to behave or act in a particular way but instead serve as behavioral nudges.…”
Section: Motivation Of the Researchmentioning
confidence: 99%
“…(2018) examined the tweets with the “vaccine” hashtag (#vaccine) from 2010 to 2016 and concluded that anti-vaccine tweets were 4.13-fold more likely to be re-tweeted than neutral tweets. Madziva et al . (2022) explored the contextual interdependence of social media platforms and behavioral changes in Africa.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation